Essential Characteristics of Media Political Discourse - N. V. Stepanova (Дискурс, 2025)
Introduction. The article presents an overview of the constitutive features of media political discourse. The aim of the article is to determine the essential parameters of modern Englishlanguage media-political discourse. The main components of this type of discourse, its axiological structure are considered. Special attention is paid to the ideological and manipulative nature of media political discourse. The relevance of the study is conditioned by the necessity of singling out media political discourse as one of the sections of discourse theory through the meticulous study of its system-forming features.Methodology and sources. As a methodological basis, the article uses some ideas of the functional approach to discourse analysis, in particular, critical discourse analysis, as well as cognitive linguistics, media discourse, medialinguistics, multimodal approach to the study of discourse. The main method is an analytical scientific review of Russian and foreign works on discourse theory.Results and discussion. According to the results of the review, the main components of media political discourse are political topics, political actors, political language, and, mainly, mass media that mediate communication within the framework of MPD. The fundamental characteristics of media political discourse include ideology, manipulativeness, persuasiveness, emotionality, polycodicity, informativeness, dynamism, and theatricality. Virtual media-political discourse, as well as Internet discourse in general, is characterized by hybridity, stylistic heterogeneity, creolization, multichannel and dialogicality, and involves remote interactive and immersive communication of virtual interlocutors. A higher level of actualization, timeliness and informativeness of online media-political discourse compared to traditional media is evident. New media supplement traditional media tasks with new functions. The axiological halo of the text, which means the whole set of values presented in the text, has a decisive impact on the interpretation of the author's ideological position and contributes to the strengthening of the media political text's suggestiveness. Based on the definition of such features of media political discourse as polycode and multilevel, it seems most effective to consider this type of discourse from the position of multimodality.Conclusion. The main function of media political discourse can be considered the construction of collective political reality in this type of discourse. Media political discourse is a construct that has constitutive power and participates in the construction of social reality. The media political picture of the world is constructed through the broadcasting of certain images, meanings, ideological attitudes, values and political preferences.